PENGARUH PENGALAMAN KERJA, INDEPENDENSI, DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT OLEH AKUNTAN PUBLIK DI SURABAYA - SETIAWAN SLAMET, IMMANUEL (: 2303-1719)
The study entitled "The Effect of Job Experience, Independency, and Competency for the Independent Auditor’s Audit Quality in Surabaya" was designed to analyze the effect of job experience, independency, and competency of the independent auditor on audit quality. The object of this research is independent auditors in Surabaya. Methods of data collection used in this research is a method of survey. The research data obtained from questionnaire data wich the amount of data are 59 respondents. The data analysis technique used is by using test validity, reliability, classical assumption and linear regression. The results showed that job experience and competency have positive effect on audit quality. So the higher the work experience which belonged to the auditor, then the higher the quality of audits produced the independent auditor and the higher the level of competence of an auditor, then the higher the quality of audits produced the independent auditor. As for how to improve the competence of the Auditors that the granting of training as well as given a chance to the auditor to attend courses or an increase in the education profession. While, independency have no effect on audit quality. This is due at the time of the inspection still not exempt from efforts of managerial (object inspection) and at the time of the preparation of the report is still often uses language or term that raises multiple interpretation. From these results, independent auditors should be concern in job experience and competence to create a good audit quality.